2011
DOI: 10.1097/iyc.0b013e31822c10e4
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Parents of Toddlers Diagnosed With Autism Spectrum Disorder in the More Than Words Parent Education Program

Abstract: A variety of parent-mediated communication intervention programs are available to families of young children with autism spectrum disorder including Hanen's More Than Words (MTW). Although the program is widely used, researchers understand little about parents' grasp of the information presented. Through a multiple case study, the unique learning experiences of 4 families who participated in MTW were examined and 6 themes emerged. Caregivers viewed MTW as a good starting point but expressed a need for explicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 20 publications
7
14
0
Order By: Relevance
“…As a result, mothers with ASD felt socially isolated as they didn't engage in social activities and kept their ASD children at home which is consistent with previous research (DePape and Lindsay 2014; Divan et al 2012;Altiere and Von Kluge 2009). In turn, this could have negative impact on their family welling (Smith et al 2012;Patterson and Smith 2011;Ekas and Whitman 2010). Despite that the current findings indicated social stigma among mothers of children with ASD, previous research showed positive societal attitudes towards individuals with ASD in Egypt (Gobrial 2015).…”
Section: Discussionsupporting
confidence: 88%
“…As a result, mothers with ASD felt socially isolated as they didn't engage in social activities and kept their ASD children at home which is consistent with previous research (DePape and Lindsay 2014; Divan et al 2012;Altiere and Von Kluge 2009). In turn, this could have negative impact on their family welling (Smith et al 2012;Patterson and Smith 2011;Ekas and Whitman 2010). Despite that the current findings indicated social stigma among mothers of children with ASD, previous research showed positive societal attitudes towards individuals with ASD in Egypt (Gobrial 2015).…”
Section: Discussionsupporting
confidence: 88%
“…Maternal mental health supports in ASD care and QoL. Studies conducted in both the high resource and LMIC settings have reported that parents who participated in any training interventions for their children with ASD consistently report a high degree of satisfaction and improvement in their children [Patterson & Smith, 2011;Perera et al, 2016;Rahman et al, 2016]. However, higher socioeconomic status of mothers and improvement in children after schooling were important contributory factors for the improvement of the QoL of mothers in our study, suggesting affordability of the families to offer ASD care through school services may influence QoL of mothers of children with ASD, and more representative studies will be needed to further parse such a relationship.…”
Section: New Evidence Of Asd In Relevance To Lmic and Contextualizatimentioning
confidence: 99%
“…Parenting a child with ASD in Egypt can have a dramatic and negative impact on the family's life, since health, social and mental health care and support for Egyptian children and young people with ASD are typically based on a household-provider model (Diggle, MaConachie, & Randle, 2003;Hartmann, 2012;Karst & Hecke, 2012;Patterson & Smith, 2011). Lack of awareness and resources in Egypt often leaves families with limited options to support their children and young people with ASD, and this can cause family isolation and frustration (Taha & Hussein, 2014).…”
Section: The Life Of Children and Young People With Asd In Egyptmentioning
confidence: 99%